2000
DOI: 10.1111/j.1745-4573.2000.tb00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Palatability Studies as Influenced by Consumer Demographics and Chevon Characteristics

Abstract: Chevon is utilized as a major meat source in many parts of the world but is consumed mostly by certain ethnic populations (Hispanics, Arabs, Indians, Pakistanis and groups from the West Indies and Africa) in the U.S. The sensory attributes of chevon from goats of different ages, weights, sex and body conformation were evaluated by a consumer panel with previous chevon consumption experiences. Tenderness scores were not affected (p> 0.05) by panelist age, sex or ethnic grouping. Income and education influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
(12 reference statements)
2
4
0
Order By: Relevance
“…The effect of sex on the sensory traits is not clear yet. In agreement with results of the present study, Germano , Madruga et al (2008) and Bonvillani et al (2010) did not find the effect of sex on the sensory traits, and contrary to them Dawkins et al (2000) and Rodrigues & Teixeira (2009) did find it. Heavier kids had significantly darker meat colour (4.77) than the lighter ones (4.24) with estimated difference for 0.5 units (P≤0.05).The meat colour score in the present study tends to increase as slaughter weight increases, as expected because as maturity increases, muscle colour becomes darker in goats (Peña et al 2009).…”
Section: Resultssupporting
confidence: 82%
“…The effect of sex on the sensory traits is not clear yet. In agreement with results of the present study, Germano , Madruga et al (2008) and Bonvillani et al (2010) did not find the effect of sex on the sensory traits, and contrary to them Dawkins et al (2000) and Rodrigues & Teixeira (2009) did find it. Heavier kids had significantly darker meat colour (4.77) than the lighter ones (4.24) with estimated difference for 0.5 units (P≤0.05).The meat colour score in the present study tends to increase as slaughter weight increases, as expected because as maturity increases, muscle colour becomes darker in goats (Peña et al 2009).…”
Section: Resultssupporting
confidence: 82%
“…Flavor score of goat meat in group A and B (3.5 ± 0.08 and 3.65 ± 0.16, respectively) appeared similar and it was prominently higher (P> 0.05) than group C (2.74 ± 0.13). Present findings are in consistent with that of reported by Dawkins, et al [28] who reported the significant effect of animal age on the flavour of cooked goat meat. However, Simela, et al [29] reported that flavour intensity increase with the age of an animal, though disagree on which age group are the most acceptable.…”
Section: Influence Of Glycogen Level On Sensory Characteristics Of Goatsupporting
confidence: 94%
“…The effect of the sex on the sensory attributes is not clear. Kirton (1970) and Dawkins et al (2000) found significant differences between sexes, while Germano and Madruga et al (2008) did not. In the present study, sex did not affect (p > 0.05) sensory scores of the LTL muscle, although the meat from males had higher amount of IMF.…”
Section: Discussionmentioning
confidence: 85%